2011
DOI: 10.1111/j.1574-0862.2011.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional crops, traditional constraints: The long‐term welfare impacts of export crop adoption among Guatemalan smallholders

Abstract: This article documents the long-term welfare effects of household nontraditional agricultural export (NTX) adoption. We use a panel dataset that spans the period 1985-2005, and employ difference-in-differences estimation to investigate the long-term impact of nontraditional agricultural export adoption on changes in household consumption status and asset position in the Central Highlands of Guatemala. Given the heterogeneity in adoption patterns, the analysis differentiates the impact estimates based on a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Commercialization of agriculture is an important means of enhancing crop productivity, food security, and nutrition reduce poverty and incomes (Gebremedhin, Jaleta, & Hoekstra, ; Läpple, Hennessy, & Newman, ; Muriithi & Matz, ; Pingali, ). Carletto, Kilic, and Kirk () present evidence on the long‐term effects of agricultural commercialization on household welfare by using panel data and focus on the nontraditional agricultural export crop in the Central Highlands of Guatemala. Bellemare () also found that contract farming, a form of commercialization, has a positive impact on household welfare in Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…Commercialization of agriculture is an important means of enhancing crop productivity, food security, and nutrition reduce poverty and incomes (Gebremedhin, Jaleta, & Hoekstra, ; Läpple, Hennessy, & Newman, ; Muriithi & Matz, ; Pingali, ). Carletto, Kilic, and Kirk () present evidence on the long‐term effects of agricultural commercialization on household welfare by using panel data and focus on the nontraditional agricultural export crop in the Central Highlands of Guatemala. Bellemare () also found that contract farming, a form of commercialization, has a positive impact on household welfare in Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…Others (Carletto et al, 1999, Carletto et al, 2010, Carletto et al, 2011) focused more on the determinants of the commercialization process and its impact on poverty, as opposed to food security and nutrition.…”
mentioning
confidence: 99%
“…Increased income and saving generated by commercialisation is likely to lead to improved household well-being; for example, increased household income has been linked to improved nutritional status of children, better health care, and improved housing condition (Braun and Kennedy, 1994;Kennedy, Bouis, and von Braun, 1992;Kennedy and Peters, 1992;Kennedy and Cogill, 1987). A recent study by Carletto, Kilic, and Kirk (2011) found general improvement in welfare levels, consumption, and livelihoods among Guatemalan smallholders who adopted non-traditional export crops including high-value vegetables and counter-seasonal fruit. Increased income from cash crops may allow farm households to invest more in farm and non-farm activities resulting in increased income generation over time.…”
Section: Household Effectsmentioning
confidence: 99%